S8-Mediated Cyclization of Bis(2-aminophenyl) Disulfide/Diselenide with Arylacetylenes/Styrenes: Access to 2-(Arylmethyl)-1,3-benzothiazoles/benzoselenazoles - Gan, Haifeng; Feng, Caojian; Zhao, Lihuan; Cao, Mengru; Wu, Hongli (Synlett, 2021)
A novel S8-mediated approach to benzothiazoles/benzoselenazoles from bis(2-aminophenyl) disulfides/diselenides and phenylacetylenes or styrenes has been developed. 2-(Arylmethyl)-1,3-benzoselenazoles were comprehensively synthesized for the first time. The reactions proceeded in moderate to excellent yields, and with a gram-scale application.
Keywords: benzothiazoles; benzoselenazoles; aralkynes; styrenes; cyclization; sulfur